2020
DOI: 10.1177/1071100719899050
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Subtalar Distraction Arthrodesis for the Treatment of Subtalar Arthritis

Abstract: Background: Subtalar distraction arthrodesis (SDA) was developed as a means of treating the symptoms of subtalar arthritis. Despite almost 30 years of research in this field, many controversies still exist regarding SDA. The objective of this study was to present an overview of outcomes following SDA, focusing on surgical technique as well as clinical and radiographic results. Methods: MEDLINE and EMBASE were queried and data abstraction was performed by 2 independent reviewers. Inclusion criteria for the arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…7,29,36 This complication is especially encountered in case of distraction and interposition of bone graft due to tension of the nerve. 17,36 In our series, 1 patient (5%) reported dysesthesia along the lateral side of the foot. Revision and nerve dissection were required because of pain persistence despite conservative measures.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…7,29,36 This complication is especially encountered in case of distraction and interposition of bone graft due to tension of the nerve. 17,36 In our series, 1 patient (5%) reported dysesthesia along the lateral side of the foot. Revision and nerve dissection were required because of pain persistence despite conservative measures.…”
Section: Discussionmentioning
confidence: 57%
“…4 In this study, no allograft was used, as several reports have shown that autograft is superior in union rates compared with allograft. 15 Nevertheless, a systematic review of subtalar distraction arthrodesis performed by Fletcher et al 17 stated that recent studies have observed identical union rates using allograft. The choice of the adequate osteosynthesis implant and the optimal positioning are also leading factors in the operation success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations